Step-by-step explanation
To solve this problem, we must apply Bayes Theorem, which states that:
![P(A|B)=\fracA){P(A)P(B|A)+P(\bar{A})P(\bar{B}|\bar{A)}}.](https://img.qammunity.org/2023/formulas/mathematics/college/kdxn0b0s2e4ys2odvyr7hnhg7szos0ks34.png)
We define the events:
• A = has the disease,
,
• B = test positive.
From the statement, we know that:
• the disease has an incidence rate of 0.1% → P(A) = 0.1% = 0.001 → P(not A) = 99.9% = 0.999,
• anyone who has the disease will test positive → P(B | A) = 100% = 1,
• the false positive rate is 1% → P(not A) = 1% = 0.01,
,
• the false-negative rate is 6% → P(not B | not A) = 6% = 0.06.
Replacing these values in the formula above, we get:
![P(A|B)=(0.001*1)/(0.001*1+0.999*0.06)\cong0.016.](https://img.qammunity.org/2023/formulas/mathematics/college/r5gankejead2nmf3floxl1mn2joh7nil0x.png)
Answer
The probability that a person who tests positive actually has the disease is approximately 0.016.